2015
DOI: 10.1111/ijs.12579
|View full text |Cite
|
Sign up to set email alerts
|

European Stroke Organisation (ESO) Guidelines for the Management of Temperature in Patients with Acute Ischemic Stroke

Abstract: Background Hyperthermia is a frequent complication in patients with acute ischemic stroke. On the other hand, therapeutically induced hypothermia has shown promising potential in animal models of focal cerebral ischemia. This Guideline Document presents the European Stroke Organisation guidelines for the management of temperature in patients with acute ischemic stroke. Methods A multidisciplinary group identified related questions and developed its recommendations based on evidence from randomized controlled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 40 publications
0
29
0
4
Order By: Relevance
“…Hyperthermia is a common complication of AIS occurring in up to 50% of patients and is associated with a poorer prognosis [19]. The processes determining the brain temperature in AIS have not been fully elucidated [20,21].…”
Section: Strokementioning
confidence: 99%
See 1 more Smart Citation
“…Hyperthermia is a common complication of AIS occurring in up to 50% of patients and is associated with a poorer prognosis [19]. The processes determining the brain temperature in AIS have not been fully elucidated [20,21].…”
Section: Strokementioning
confidence: 99%
“…Moderate hypothermia (32-33 o C), as opposed to mild hypothermia (34-35 o C), seems to lead to complications more commonly (hypotension, cardiac arrhythmias, pneumonia or thrombocytopenia) [45]. Likewise, the European Stroke Organisation does not recommend induced hypothermia as a measure either to improve the functional status or to lengthen the survival of AIS patients [19]. Moreover, there is no explicit answer to the question regarding temperature reductions in stroke patients; some issues are still unclear, i.e.…”
Section: Application Of Hypothermiamentioning
confidence: 99%
“…The meta-analysis of Ntaios et al [102] that included 4 major randomized trials [103106] found no difference in mortality or neurological outcome between hypothermia and hyperthermia (>38 °C).…”
Section: Resultsmentioning
confidence: 99%
“…126 Hypothermia, a proven multimodal, effective physical approach to cytoprotection needs to be retested in this model. 127 Although there are no currently accepted adjuvant pharmacological treatments for acute stroke currently, this is a future blank-slate area for clinical research.…”
Section: Acute Stroke Treatments: Endovascular Treatmentsmentioning
confidence: 99%